2022
DOI: 10.1108/apjml-07-2021-0486
|View full text |Cite
|
Sign up to set email alerts
|

What are the most important consumer decision factors when choosing an airline? An emerging economy perspective

Abstract: PurposeThe quest to acquire new customers and retain the existing ones is a challenge for all aviation companies. This paper attempts to assist the aviation companies in tackling this challenge by revealing the most important factors that their customers consider to be the most important while making purchasing choices.Design/methodology/approachDrawing on three separate studies, this paper identifies the most important factors that influence consumers' choice of airlines in an emerging economy context. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…The advent of streaming platforms such as Netflix, Amazon Prime Video, and Hulu has fundamentally transformed the way individuals consume entertainment during their travels. Thanks to the availability of an extensive collection of films, television programs, and documentaries, travelers now have the ability to enjoy their favorite entertainment at any time and in any location (Banerji et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of streaming platforms such as Netflix, Amazon Prime Video, and Hulu has fundamentally transformed the way individuals consume entertainment during their travels. Thanks to the availability of an extensive collection of films, television programs, and documentaries, travelers now have the ability to enjoy their favorite entertainment at any time and in any location (Banerji et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of applications is crucial for gaining a deeper comprehension of traveler behavior and preferences. These applications allow for the analysis of data obtained from mobile apps provided by airports, airlines, or other travel-related enterprises (Banerji et al, 2023). Track the frequency of usage for features such as mobile check-in, real-time flight updates, access to airport lounges, and luggage tracking.…”
Section: Discussionmentioning
confidence: 99%
“…Familiarity with airlines increases the brand trust of customers which urges them to choose the most familiar airline (Law et al, 2022). Familiarity exists in the airline sector more than in any other means of transportation as airline customers are more concerned about their safety, the comfort of travel, on-time arrival, customer care quality, crew friendliness and ease of bookings (Banerji et al, 2023). It is further added by Arthur (2020) as well that although customers are inclined to airlines, but still they prefer their familiar brands.…”
Section: Brand Familiaritymentioning
confidence: 99%
“…Quality designs can lead to a positive service experience in the core service attributes such as aircraft, cabin space and cabin seats. According to Banerji et al [35], their study found that customers consider the type of aircraft as an important factor when choosing flights. Aircraft design and consumption of the service converge to form a good service experience.…”
Section: Mediating Role Of Quality Designs On the Relationship Betwee...mentioning
confidence: 99%